A language of dragons / S.F. Williamson. - Williamson, S. F. (Stephanie F.) (Harper Fire, 2025)
London, 1923. Dragons soar through the skies and protests erupt on the streets, but Vivien Featherswallow isn't worried. She's going to follow the rules, get an internship studying dragon languages and make sure her little sister never has to risk growing up Third Class. By midnight, Viv has started a civil war. With her parents arrested and her sister missing, all the safety Viv has worked for is collapsing around her. So when a lifeline is offered in the form of a mysterious 'job', she grabs it. But the more she learns, the more she realises that the bubble she's grown up in isn't as safe as she thought.